The Implementation of Collaborative Strategy in Teaching Students’ Speaking Skill - Chrismaretta, Chrismaretta; Abrar, Mukhlas (EduInovasi: Journal of Basic Educational Studies, 2024)
Effective communication relies heavily on one's speaking ability, which is crucial not only in one's native language but also foreign languages, especially challenging during the secondary school years. This study aimed to improve students' speaking comprehension through a collaborative learning approach. Using qualitative research methods, data were collected through questionnaires from eleventh grade students of SMAN 2 Muara Bungo in the 2023/2024 academic year. The sample consisted of one class, namely class XI IPA, which consisted of 36 students from a total population of 90 students. The findings demonstrate the efficacy of collaborative strategies in improving speaking comprehension, fostering students' confidence in articulating ideas during the learning process. Collaborative learning facilitates the production of more argument components, leading to a higher level of discourse. In addition, it enhances students' cognitive ability to remember, understand, apply and analyze information. Therefore, collaborative learning emerges as a promising classroom strategy to improve students' speaking comprehension. However, various challenges and variables affect students' success in utilizing collaborative strategies for English language learning.